Surgical management of humeral shaft nonunions. Success of a consistent protocol over 17 years. Issue 12 (December 2021) - Zalavras, Charalampos G.; Yasmeh, Siamak; Bougioukli, Sofia
Highlights: Healing of aseptic nonunions of the humeral shaft can reliably be achieved by stable plate fixation and augmentation of local biology. Stable fixation can be achieved with a single plate (4.5 mm LCP in most cases) without the need for double plating or allograft struts. Careful dissection of the radial nerve starting distal to the nonunion in healthy tissue can minimize iatrogenic radial nerve palsy. Abstract: Introduction: Surgical treatment of humeral shaft nonunions is characterized by variability of fixation methods, graft choices, and rates of union and iatrogenic radial nerve palsy. The aim of the current study is to evaluate the union rate of humeral shaft aseptic nonunions and the rate of postoperative complications following a consistent management protocol. Patients and methods: This is a retrospective review of 41 consecutive adult patients (23 female and 18 male with a mean age of 42 years) with aseptic nonunions of the humeral shaft treated by the senior author in our institution over a 17-year period. Nonunions were located in the middle third of the diaphysis in 33 patients, in the distal third in 6, and in the proximal third in 2 patients. Comorbidities were present in 49% of patients and the most common were smoking in 27% and diabetes mellitus in 17% of patients. Patients were treated at an average of 24 months after their injury. Surgical protocol consisted of careful dissection of the radial nerve, debridement of the nonunion site, stable plate fixation and augmentation of local biology. Results: Thirty-eight patients had mean clinical and radiographic follow-up of 9.4 months. All 38 nonunions healed at a mean time of 3.5 months. There were no persistent nonunions and no failures of fixation. None of the 40 patients with an intact radial nerve preoperatively developed any signs of radial nerve compromise after surgery. Complications consisted of one superficial infection (2%) that resolved with oral antibiotics and one deep infection (2%) that required implant removal and debridement. The mean pain score on the visual analog scale was 0.7. Mean elbow range of motion was 125 degrees with a mean extension deficit of 5 degrees and mean flexion of 130 degrees. Conclusions: Our surgical protocol achieved consistent healing of nonunions of the humeral shaft with a low complication rate and no iatrogenic radial nerve palsy, even in long-standing nonunions in patients with comorbidities.